Far out fables. Chicken Little saves the moon base : a graphic novel - Harper, Benjamin (Stone Arch Books, 2021)
In this graphic novel adaptation of the classic fable, Chicken Little notices a small dip in oxygen levels at the moon base and fears that may mean big trouble, but will her friends believe her? Includes information about the original story, visual questions, and glossary.